Vulnerability and risk assessment of lead (Pb) concentrations in drinking water via statistical and geostatistical analyses - Shakoor, Huma; Alshehri, Fahad; Shahab, Muhammad; Abanumay, Faris A.; Ali, Liaqat (Frontiers in Water, 2025)
IntroductionLead (Pb) contamination in drinking water poses serious public health risks, particularly when concentrations exceed the WHO permissible exposure limit (PEL) of 0.01 mg/L (10 ppb). This study investigates Pb levels in drinking water sources across five districts Kohat, Hangu, Dera Ismail Khan (D.I. Khan), Bannu, and Karak to assess contamination severity, spatial distribution, and potential health risks.MethodsDrinking water samples were collected from multiple locations within the five districts and analyzed for Pb concentrations. Statistical analyses, including one-way ANOVA and the Shapiro-Wilk normality test, were conducted to evaluate variations and data distribution. Health risk assessment was performed using estimated daily intake (EDI) and hazard quotient (HQ) calculations. Additionally, geospatial analysis using Inverse Distance Weighting (IDW) modeling was employed to identify contamination hotspots.ResultsAll districts exceeded the WHO PEL for Pb, with the highest mean concentrations recorded in Bannu (0.720 mg/L) and Karak (0.693 mg/L). Maximum Pb levels reached 1.809 mg/L in Bannu and 1.572 mg/L in Karak. Exceedance rates were 100% in Hangu, Bannu, and Karak. ANOVA analysis (p-value = 8.16 × 10−11) indicated significant variations among districts, while the Shapiro-Wilk test (W = 0.742, p-value < 0.0001) confirmed non-normal data distribution. Health risk assessment revealed critical risks, particularly for children, with HQ values exceeding safe thresholds, notably in Bannu and Karak. Geospatial modeling identified contamination hotspots, including Jozara Water (Hangu), Mufti Mehmood Circuit House (D.I. Khan), and Kalanger (Bannu).Discussion and conclusionThe findings highlight widespread Pb contamination in drinking water across the study area, posing severe health risks. Immediate intervention through advanced water treatment, stringent regulatory enforcement, and continuous monitoring is essential to safeguard public health.